Product of the Pseudomonas aeruginosa gene pilD is a prepilin leader peptidase. - Nunn, D N (1991)
The related type IV pilins produced by Pseudomonas aeruginosa, Neisseria gonorrhoeae, Bacteroides nodosus, and Moraxella bovis are synthesized as precursors with short, six- or seven-amino acid N-terminal leader peptides. We have previously observed that P. aeruginosa mutations in pilD, a gene required for pilus biogenesis, result in the accumulation of unprocessed prepilin in the membrane and a general defect in the excretion of a number of extracellular enzymes. An endopeptidase activity has been detected in detergent-solubilized inner membrane of P. aeruginosa and shown to correctly cleave the prepilin of P. aeruginosa and N. gonorrhoeae. It is absent from pilD mutants, increased by pilD overexpression, and conferred on Escherichia coli by the introduction of the pilD gene. The pilD gene product, purified by immunoaffinity chromatography with antibody to a PilD-derived synthetic peptide, was identified with the endopeptidase. PilD appears to be a prototype of a class of enzymes that process not only type IV pilin precursors but also components of a protein-excretion apparatus of Gram-negative bacteria.